Analysis Discourse of “Blarak” Short Story by Yanusa Nugroho - Sofyaningrum, Rosita; Azizah, Ririn Nurul; Filyang, Rissa; As'ad, Muhammad (English Education and Literature Journal (E-Jou), 2023)
In communicating, humans sometimes need to show directly what they mean. The use of language in communication between humans in dating is a form of discourse. Besides discourse being a form of language use, discourse is also an utterance. Discourse analysis based on context is, of course, inseparable from the use of pragmatics. Pragmatic discourse analysis in literary works has been done—analysis of the novel Bumi Manusia by Pramodya Ananta Tour, translated into English by Max. This study aims to analyze discourse with a pragmatic approach in the short story Blarak by Yanusa Nugroho. The type of research used in this research is descriptive qualitative research. The data of this study are the words or sentences contained in the short story Blarak by Yanusa Nugroho which are contained in the 2009 Kompas short story collection. The data collection technique in this study used note-taking techniques. This study's research instrument (data collection instrument) is from the researcher himself. The analysis technique used in this study is a qualitative data analysis technique. Based on the research results, it can be concluded that the deixis in the short story Blarak by Yanusa Nugroho includes personal deixis, place deixis, and time deixis. Keywords: analysis, discourse, short story